Flavonoid Compounds of Buah Merah (Pandanus conoideus Lamk) as a Potent Oxidative Stress Modulator in ROS-induced Cancer: In Silico Approach - Abd. Kakhar Umar; Faruk Jayanto Kelutur; James H. Zothantluanga (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Buah Merah, a typical fruit from Papua, Indonesia which is used empirically in cancer therapy is rich in carotenoids and flavonoids. However, the mechanisms by which Buah Merah ameliorates cancer remained unknown. Natural antioxidant enzymes and pro-oxidant enzymes modulation significantly suppressed ROS production and cancer growth. Therefore, the determination of target enzymes of Buah Merah contents was studied through an in silico approach. Carotenoid and flavonoid compounds from Buah Merah were docked to 7 ROS modulating enzymes using Autodock Vina and the interaction stability was studied using the CABS Flex 2.0 server. The crucial amino acids of each enzyme were determined using DockFlin and prediction of acute oral toxicity of each test ligand was studied using ProTox-II. Based on the molecular docking results, quercetin 3'-glucoside is the most potent compound in binding to CAT, GR, GPx, SOD, LOX, and NOX with binding energy values of -11.2, -9.7, -8.6, -10.2, -10.7, and -12.8 kcal/mol, respectively. Meanwhile, taxifolin 3-O-α-arabinopyranose produced the highest binding affinity of -10.0 kcal/mol at the XO. Each test ligand formed stable interactions with ROS modulating enzymes and formed bonds with crucial amino acids resulting in strong adhesion compared to native and reference ligands. The glucoside group of quercetin 3'-glucoside plays an essential role in determining the proper position in the attachment and supports the formation of hydrogen bonds with receptors. With low acute oral toxicity, it can be concluded that quercetin 3'-glucoside from Buah Merah is a potent oxidative stress modulator in cancer prevention and therapy.